Assessing client needs in community veterinary care: a case study from WisCARES - Schultz, Kelly; Alvarez, Elizabeth; Brooks, Jennifer; Chun, Ruthanne (Frontiers in Veterinary Science, 2025)
As community veterinary clinics expand across the United States, there is a growing recognition that services need to be aligned with the specific needs of clients and their companion animals, which may vary from one community to the next. WisCARES Community Clinic, which has served low-income pet owners in Dane County, Wisconsin for over a decade, conducted a comprehensive needs assessment in the summer of 2024 to re-evaluate the support required by its clientele. Through an interviewer-administered survey of 51 clients, conducted either in person or by phone, the study identified key areas for assistance. Clients most frequently reported needing support with pet food, treats, pet cleaning supplies, and dental care items, as well as access to affordable grooming services. In addition, many clients expressed a need for help navigating social services and securing reliable transportation. These findings highlight that clients experiencing poverty require more than basic veterinary care to maintain the health and well-being of their pets. While local contexts vary, this assessment offers valuable insight for other community veterinary programs seeking to allocate limited resources to where they will have the greatest impact.